Humanitys first healers: psychological and psychiatric stances on shamans and shamanism (Archives of Clinical Psychiatry, 2007)
BACKGROUND: the author describes shamans as practitioners who deliberately shift their phenomenological pattern of attention, perception, cognition, and awareness in order to obtain information not ordinarily available to members of the social group that granted them privileged status. OBJECTIVES: to describe how these phenomenological shifts were accomplished and used. METHODS: archival studies of shamanic literature as well as field research in communities where shamans are actively functioning. RESULTS: the source of shaman-derived information is attributed to such discarnate entities and forces as spirits, ancestors, animal guides, and energetic fields. These agencies were contacted through ritualized drumming, dancing, lucid dreaming, the use of psychotropic plants, focused attention, and other technologies. This study was important because it determined that shamans utilize the obtained information to attend to their communitys social, psychological, and medical needs. CONCLUSIONS: the ubiquitous appearance of shamans, especially in hunting and gathering tribes, indicates that their presence in a social group served adaptive functions. Further, these data can make important contributions to cognitive neuroscience, social psychology, psychotherapy, and ecological psychology.